Polyurethane adhesive as well as preparation method and application thereof
By using the synergistic effect of compound polyurethane adhesive, butyl acetate and mesoporous microspheres in the white ink hot painting process, the problems of heavy texture, poor breathability and high temperature energy consumption of clothing hot painting are solved, and the effects of softness, breathability, friction resistance and soap color resistance are achieved.
Patent Information
- Application Number
- CN202411987740.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the white ink hot painting process, the clothing hot painting clothes have a heavy texture and poor breathability. The hot melt glue powder process requires high temperature conditions, resulting in high energy consumption.
A polyurethane adhesive with low curing temperature, softness after bonding, good breathability and high adhesion, is adopted to form a crosslinking network with appropriate flexibility through the combination of Mannich polyether polyol and soft foam polyether polyol, and the breathability is improved through the synergy between butyl acetate and mesoporous microspheres.
It realizes the printing without hardness, improves the friction resistance and soap-resistant color fastness of the fabric, reduces the dry solidification temperature of the adhesive film forming, significantly improves the breathability of the printing, and makes the printed products more breathable and comfortable.
Smart Images

Figure BDA0005222971350000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane adhesives, and particularly relates to a polyurethane adhesive and a preparation method and application thereof. Background Art
[0002] In the field of clothing printing, there are three main processes: traditional screen printing and knitting, as well as the emerging white ink heat transfer. The white ink heat transfer process is to use a white ink heat transfer printer to directly print the computer-drawn pattern onto the PET film pre-coated with release agent and ink-absorbing coating, first printing the color film and then the white ink; after the powder is sprinkled and shaken by the powder shaker, the hot melt adhesive powder is evenly covered on the white ink of the pattern, and then dried, and then the white ink heat transfer is transferred to the fabric using a press, and the waste film is torn off to complete the heat transfer process. The white ink heat transfer process has the following characteristics: 1) Color freedom: In white ink heat transfer, creators can use KCMY color to use the color management software system to create and freely use various colors to make the work more vivid and bright; 2) Diverse creative techniques: White ink heat transfer can be created using a variety of materials, such as cloth, paper, leather, etc., to achieve a variety of different artistic effects and aesthetics. 3) Personalization; you can design patterns and colors according to your personal preferences; choose your favorite fabrics, whether it is a high-elastic jersey or a low-elastic advertising shirt, you can use heat transfer to print patterns.
[0003] The heat transfer process has the above-mentioned unique advantages and is replacing traditional screen printing, water slurry printing and knitting. It is gradually being widely used and recognized by the clothing printing industry, which has had a significant impact on the entire clothing printing industry. The white ink heat transfer market is growing at an alarming rate.
[0004] In the white ink heat transfer process, hot melt adhesive powder is used as the bonding between the pattern and the base material layer. The hot melt adhesive powder is evenly sprinkled on the white ink layer printed on the PET film through a powder shaking machine, baked at a high temperature of 160-180℃ to melt into a film, and then covered on the base material fabric and heat transferred at high temperature to obtain the heat transfer. Hot melt adhesive powder gives the heat transfer the advantages of good adhesion and good water fastness.
[0005] However, the disadvantage of the white ink heat transfer process is that the clothing heat transfer clothes have a heavy glue texture and poor air permeability. If the full pattern covers a large area, it will appear stuffy, affecting people's comfort when wearing it. In addition, the hot melt adhesive powder process needs to be melted under high temperature conditions and combined with the pattern to play a bonding role. High temperature conditions lead to high energy consumption during the production process. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a polyurethane adhesive with low curing temperature, softness after bonding, good air permeability and high adhesion, as well as a preparation method and application thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a polyurethane adhesive, which is made of the following raw materials in weight percentage: 35-65wt% of composite polyether polyol, 14-25wt% of polyisocyanate, 1-5wt% of hydrophilic chain extender, 1-5wt% of small molecule chain extender, 0.05-3wt% of catalyst, 0.5-4wt% of neutralizer, 1-7wt% of end-capping agent, 1-8wt% of silane coupling agent, 2-12wt% of mesoporous microspheres, 2-5% of isopropanol, 2-5wt% of butyl acetate and 0.2-4wt% of defoamer, and the balance is water;
[0009] Wherein, the composite polyether polyol is a composition of Mannich polyether polyol and soft foam polyether polyol in a mass ratio of 1: (0.5-1); the manufacturer of the soft foam polyether polyol is Shandong Bluestar Dongda Co., Ltd., the model is 10LD28XM, the number average molecular weight is 4000, and the functionality is 2; the manufacturer of the mesoporous microspheres is Shanghai Zhenzhun Biotechnology Co., Ltd., the model is MS-10040;
[0010] Preferably, the silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0011] Preferably, the polyisocyanate is hydrogenated phenylmethane diisocyanate.
[0012] Preferably, the catalyst is bismuth neodecanoate.
[0013] Preferably, the hydrophilic chain extender is 2,2-dimethylolpropionic acid (DMPA) and / or 2,2-dimethylolbutanoic acid (DMBA).
[0014] Preferably, the small molecule chain extender is at least one of 1,4-butanediol, ethylene glycol, hexanediol, diethylene glycol, ethylenediamine, and diethylenetriamine.
[0015] Preferably, the blocking agent is methyl ethyl ketone oxime.
[0016] Preferably, the neutralizing agent is triethylamine.
[0017] In a second aspect, the present invention provides a method for preparing the polyurethane adhesive according to the first aspect, comprising the following steps:
[0018] S1. Stir the polyether polyol, hydrophilic chain extender, silane coupling agent and mesoporous microspheres in a nitrogen atmosphere, then add polyisocyanate and catalyst, continue stirring and reacting at 70-95° C. for 1-4 hours, and then cool the reaction product to 60-70° C. for standby use;
[0019] S2, adding a small molecule chain extender to the product obtained in S1, and then stirring the reaction for 1-2 hours, and gradually heating to 85-90°C;
[0020] S3, adding the end-capping agent to the product obtained in S2, continuing to stir and react for 1-3 hours, then adding a neutralizing agent at room temperature, and adding water, butyl acetate and isopropanol for ultrasonic dispersion to obtain an aqueous polyurethane emulsion;
[0021] S4, adding a defoamer to the aqueous polyurethane emulsion prepared in S3, dispersing and stirring, to obtain the polyurethane adhesive.
[0022] Preferably, in step S1, the stirring speed is 500-600 rpm.
[0023] Preferably, in step S2, the stirring speed is 500-600 rpm, and the stirring time is 10-30 min.
[0024] Preferably, in step S3, the stirring speed is 500-600 rpm, the ultrasonic power is 200-250 W, and the ultrasonic time is 5-10 min.
[0025] Preferably, in step S4, the stirring speed is 500-600 rpm, and the stirring time is 10-30 min.
[0026] In a third aspect, the present invention provides use of the polyurethane adhesive described in the first aspect in preparing clothing heat transfer coating ink.
[0027] Adhesive of the present invention is waterborne polyurethane, and it adopts Mannich polyether polyol and soft foam polyether polyol as polyether polyol, and both are compounded with good reactivity.Meanwhile, the flexible segment that soft foam polyether polyol provides can make whole system more easily deform under external forces such as stretching, and the rigid structure (aromatic ring structure) of Mannich polyether polyol can play a certain supporting role, prevent material from excessive deformation and lose strength, Mannich polyether polyol and soft foam polyether polyol form a cross-linked network with appropriate flexibility in collaboration, after the adhesive is added to inkjet and applied to clothing heat transfer, its printing will not bring stiff feeling to clothing, overcome the problem that hot melt powder and ink compound can make printing feel too poor, make wearing more comfortable.In addition, soft foam polyether polyol and Mannich polyether polyol synergistically, can make adhesive and ink, fabric form better interface bonding, reduce interface defects, improve adhesion, so that fabric has good friction resistance and soap-resistant color fastness.
[0028] The use of butyl acetate and mesoporous microspheres in the present invention can significantly improve the air permeability of the printing, because butyl acetate can reduce the surface tension of the system during the foaming process, so that the bubbles are more likely to break during the formation process to form an open-pore structure, and the boiling point of butyl acetate is 126°C, which is higher than the boiling point of water, but lower than the curing temperature of 130-140°C, so butyl acetate will volatilize during the curing film formation of the adhesive, thereby leaving breathable micropores in the polyurethane film layer, improving the air permeability, making the polyurethane have good open porosity, allowing air and moisture to circulate better, and improving the comfort of use; and the mesoporous microspheres use the mesoporous structure of the mesoporous microspheres to achieve gas permeability, further improving the air permeability of the adhesive, so after the adhesive is made into ink, the air permeability of the printing can be significantly improved, making the printed product more breathable and comfortable. Isopropyl alcohol is used as a cosolvent to increase the solubility of butyl acetate in water. One end of the silane coupling agent can react with the hydroxyl group on the surface of the mesoporous microsphere to form a covalent bond, and the other end can react with the organic group in the polyurethane resin. This "bridging" effect can significantly improve the interfacial bonding strength between the filler and the polyurethane matrix.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The water-based polyurethane adhesive of the present invention uses Mannich polyether polyol and soft foam polyether polyol as polyether polyols, and the two cooperate to form a cross-linked network with appropriate flexibility. After being applied to clothing heat transfer, the printing has no stiffness, overcoming the problem of poor composite feel of hot melt powder and ink, making it comfortable to wear, and improving the friction resistance and soap washing color fastness of the fabric. At the same time, the use temperature of the polyurethane adhesive in the present invention is between 130-140°C, and the curing time is less than 3 minutes, which is significantly lower than the temperature (above 180°C) at which the hot melt adhesive powder melts to form a film, and can avoid the influence of high temperature on the fabric and high energy consumption.
[0031] (2) The present invention uses butyl acetate and mesoporous microspheres to synergistically improve the air permeability of the polyurethane adhesive. After the adhesive of the present invention is made into ink, the adhesive has good open porosity, which is conducive to the circulation of air and moisture, thereby improving the comfort of use.
[0032] (3) The adhesive of the present invention can replace hot melt adhesive powder in clothing heat transfer, and can improve the softness, air permeability, friction resistance and soap washing color fastness of fabric heat transfer printing. At the same time, it can significantly reduce the film-forming and curing temperature of the adhesive. DETAILED DESCRIPTION
[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0034] The sources of the raw materials and equipment used in the embodiments and comparative examples are as follows:
[0035] Mannich polyether polyol: manufacturer is Jiahua Chemical (Shanghai) Co., Ltd., model is Purabiol RC5335, viscosity is 900-1500mPa·s / 25℃;
[0036] Soft foam polyether polyol: the manufacturer is Shandong Bluestar Dongda Co., Ltd., the model is 10LD28XM, the number average molecular weight is 4000, and the functionality is 2;
[0037] Mesoporous microspheres: molecular sieve, manufacturer: Shanghai Zhenzhun Biotechnology Co., Ltd., model: MS-10040, specific surface area: 350-450m 2 / g, pore size: 0.56-0.58nm, crystallinity: >95%, particle size: 100-300nm;
[0038] β-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane: manufacturer is Hangzhou Jessica Chemical Co., Ltd., model number is KH-1771;
[0039] Butyl acetate: manufacturer is Shanghai Yien Chemical Technology Co., Ltd., model number is R007184;
[0040] Bismuth neodecanoate: manufacturer is Shandong Lanyue New Material Technology Co., Ltd., model number is LK-5;
[0041] Hydrogenated phenylmethane diisocyanate: manufacturer is Covestro, model is DesmodurH12MDI;
[0042] 2,2-Dihydroxymethylpropionic acid: manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., model number is 1033326;
[0043] 2,2-Dihydroxymethylbutyric acid: manufacturer is Shanghai Haohong Biopharmaceutical Technology Co., Ltd., model number is 1014884;
[0044] 1,4-Butanediol: The manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is PB04152;
[0045] Ethylene glycol: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is MB00660;
[0046] Triethylamine: manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd., model number is GB00816;
[0047] Methyl ethyl ketone oxime: manufacturer Honeywell, brand name MEKO
[0048] Polyether siloxane defoamer: manufacturer is German Digo, model 825;
[0049] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0050] Example 1
[0051] A polyurethane adhesive is prepared from the following raw materials in percentage by weight: 55wt% of composite polyether polyol, 20wt% of polyisocyanate, 3wt% of hydrophilic chain extender, 3wt% of small molecule chain extender, 1wt% of catalyst, 2wt% of neutralizer, 5wt% of end-capping agent, 6wt% of silane coupling agent, 10wt% of mesoporous microspheres, 4wt% of isopropanol, 4wt% of butyl acetate and 3wt% of defoamer, and the balance is water; wherein the composite polyether polyol is a composition of Mannich polyether polyol and soft foam polyether polyol in a mass ratio of 1:0.8;
[0052] Wherein, the polyisocyanate is hydrogenated phenylmethane diisocyanate, the hydrophilic chain extender is 2,2-dihydroxymethylpropionic acid, the small molecule chain extender is 1,4-butanediol, the catalyst is bismuth neodecanoate, the neutralizer is triethylamine, the end-capping agent is methyl ethyl ketone oxime, the silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the mesoporous microspheres are molecular sieves, and the defoamer is a polyether siloxane defoamer;
[0053] The preparation method of the polyurethane adhesive comprises the following steps:
[0054] S1, polyether polyol, hydrophilic chain extender, silane coupling agent and mesoporous microspheres were stirred at 550 rpm in a nitrogen atmosphere, and then polyisocyanate and catalyst were added, and the reaction was continued at 80° C. with stirring for 3 h, and then the reaction product was cooled to 65° C. for standby use;
[0055] S2, adding a small molecule chain extender to the product obtained in S1, then stirring at a speed of 550 rpm for 1.5 h and gradually heating to 85° C.;
[0056] S3, adding the end-capping agent to the product obtained in S2, continuing the reaction for 2 hours, then adding a neutralizing agent at room temperature, and adding water, isopropanol and butyl acetate, and ultrasonically dispersing at a power of 200 W for 8 minutes to obtain an aqueous polyurethane emulsion;
[0057] S4. After adding a defoamer to the aqueous polyurethane emulsion prepared in S3, the mixture was dispersed and stirred at a rotation speed of 550 rpm for 20 minutes to obtain the polyurethane adhesive.
[0058] Example 2
[0059] A polyurethane adhesive is prepared from the following raw materials in percentage by weight: 35wt% of composite polyether polyol, 14wt% of polyisocyanate, 1wt% of hydrophilic chain extender, 1wt% of small molecule chain extender, 0.05wt% of catalyst, 0.5wt% of neutralizer, 1wt% of end-capping agent, 1wt% of silane coupling agent, 2wt% of mesoporous microspheres, 2% of isopropanol, 2wt% of butyl acetate and 0.2wt% of defoamer, and the balance is water; wherein the composite polyether polyol is a composition of Mannich polyether polyol and soft foam polyether polyol in a mass ratio of 1:0.5;
[0060] Wherein, the polyisocyanate is hydrogenated phenylmethane diisocyanate, the hydrophilic chain extender is 2,2-dihydroxymethylbutyric acid, the small molecule chain extender is ethylene glycol, the catalyst is bismuth neodecanoate, the neutralizer is triethylamine, the end-capping agent is methyl ethyl ketone oxime, the silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the mesoporous microspheres are molecular sieves, and the defoamer is a polyether siloxane defoamer;
[0061] The preparation method of the polyurethane adhesive comprises the following steps:
[0062] S1. Stir the polyether polyol, hydrophilic chain extender, silane coupling agent and mesoporous microspheres at 500 rpm in a nitrogen atmosphere, then add polyisocyanate and catalyst, continue stirring and reacting at 70° C. for 4 h, and then cool the reaction product to 60° C. for standby use;
[0063] S2, adding a small molecule chain extender to the product obtained in S1, then stirring at 500 rpm for 1 h and gradually heating to 85°C;
[0064] S3, adding the end-capping agent to the product obtained in S2, continuing the reaction for 3 hours, then adding a neutralizing agent at room temperature, and adding water, isopropanol and butyl acetate, and ultrasonically dispersing at a power of 200 W for 10 minutes to obtain an aqueous polyurethane emulsion;
[0065] S4. Add a defoamer to the aqueous polyurethane emulsion prepared in S3, and disperse and stir at a rotation speed of 500 rpm for 30 minutes to obtain the polyurethane adhesive.
[0066] Example 3
[0067] A polyurethane adhesive is prepared from the following raw materials in percentage by weight: 65wt% of composite polyether polyol, 25wt% of polyisocyanate, 5wt% of hydrophilic chain extender, 5wt% of small molecule chain extender, 3wt% of catalyst, 4wt% of neutralizer, 7wt% of end-capping agent, 8wt% of silane coupling agent, 12wt% of mesoporous microspheres, 5% of isopropanol, 5wt% of butyl acetate and 4wt% of defoamer, and the balance is water; wherein the composite polyether polyol is a composition of Mannich polyether polyol and soft foam polyether polyol in a mass ratio of 1:1;
[0068] Wherein, the polyisocyanate is hydrogenated phenylmethane diisocyanate, the hydrophilic chain extender is 2,2-dihydroxymethylbutyric acid, the small molecule chain extender is 1,4-butanediol, the catalyst is bismuth neodecanoate, the neutralizer is triethylamine, the end-capping agent is methyl ethyl ketone oxime, the silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the mesoporous microspheres are molecular sieves, and the defoamer is a polyether siloxane defoamer;
[0069] The preparation method of the polyurethane adhesive comprises the following steps:
[0070] S1. Stir the polyether polyol, hydrophilic chain extender, silane coupling agent and mesoporous microspheres at 600 rpm in a nitrogen atmosphere, then add polyisocyanate and catalyst, continue stirring and reacting at 95° C. for 1 h, and then cool the reaction product to 70° C. for standby use;
[0071] S2, adding a small molecule chain extender to the product obtained in S1, and then stirring at a speed of 600 rpm for 1 h and gradually heating to 90°C;
[0072] S3, adding the end-capping agent to the product obtained in S2, continuing the reaction for 1 hour, then adding a neutralizing agent at room temperature, and adding water, isopropanol and butyl acetate, and ultrasonically dispersing at a power of 250 W for 5 minutes to obtain an aqueous polyurethane emulsion;
[0073] S4. Add a defoamer to the aqueous polyurethane emulsion prepared in S3, and disperse and stir at a rotation speed of 600 rpm for 10 minutes to obtain the polyurethane adhesive.
[0074] Comparative Example 1
[0075] The difference between Comparative Example 1 and Example 1 is that: no Mannich polyether polyol is added, and the missing amount is supplemented by soft foam polyether polyol.
[0076] Comparative Example 2
[0077] The difference between Comparative Example 2 and Example 1 is that no soft foam polyether polyol is added, and the missing amount is supplemented by Mannich polyether polyol.
[0078] Comparative Example 3
[0079] The difference between Comparative Example 3 and Example 1 is that the total amount of the composite polyether polyol remains unchanged, and the mass ratio of the composition of the Mannich polyether polyol and the soft foam polyether polyol is 0.8:1.
[0080] Comparative Example 4
[0081] The difference between Comparative Example 4 and Example 1 is that butyl acetate and mesoporous microspheres are not added.
[0082] Comparative Example 5
[0083] The difference between Comparative Example 5 and Example 1 is that butyl acetate is not added.
[0084] Comparative Example 6
[0085] The difference between Comparative Example 6 and Example 1 is that no mesoporous microspheres are added.
[0086] Performance Testing
[0087] The binders of Examples 1-3 and Comparative Examples 1-6 were made into coating inks, specifically as follows:
[0088] The coating ink includes the following raw materials in weight percentage: 30% adhesive of each group, 8% pigment, 35% humectant, 1.5% surfactant, 0.1% pH adjuster, 0.1% preservative, and the balance is water; wherein the humectant is propylene glycol and ethylene glycol in a mass ratio of 1:1; the surfactant is Surfynol 104E; the pH adjuster is triethanolamine; the preservative is isothiazolone; the pigment is a purple-red pigment, prepared by pre-dispersing a mixture of Pigment Red 254 and Pigment Red 202 in a vinyl copolymer carrier resin to form a solid magenta pigment, the manufacturer is BASF, and the model is Microlith 4330K.
[0089] The coating ink made of the adhesive of Examples 1-3 and Comparative Examples 1-6 was used for printing performance test, and the Caishen Xingguang 3204SG inkjet printer was used for printing test, and the nozzle was Xingguang 1024; the printing medium was 12A woven cotton cloth; after printing, the color was fixed at 80°C for 8 minutes to obtain 8 groups of cloth samples of Examples 1-3 and Comparative Examples 1-6.
[0090] 1. Color fastness test
[0091] The color fastness to washing with soap and soap was measured according to GB / T 3921-2008 “Textiles - Tests for Color Fastness - Color Fastness to Washing with Soap”, and the color fastness to rubbing was measured according to GB / T 3920-2008 “Fabrics - Tests for Color Fastness - Color Fastness to Rubbing”, as shown in Table 1 for details.
[0092] 2. Stiffness test
[0093] Cut a 20cm×2.5cm fabric sample at the printed pattern. Place it flat on the stiffness tester platform with the front side facing up, align one end of the sample with the front edge of the platform, and place a graduated pressing plate. The pressing plate drives the sample to move forward synchronously at a speed of 0.3-0.5cm / s. When one end of the sample droops to just touch the test line, stop moving and record the length (cm), as shown in Table 1.
[0094] 3. Printing air permeability test
[0095] The air permeability of the fabric at the printed pattern was measured on a fully automatic air permeability meter according to GB / T 5453-1997 “Determination of air permeability of textile fabrics” (mm / s). The test conditions were a hole area of 20 cm 2 , the pressure is 100Pa, see Table 1 for details.
[0096] 4. Curing time and temperature test
[0097] After mixing the A and B components of Examples 1-3 and Comparative Examples 1-6 to obtain the adhesive, the solidification time in the container, i.e., the operation time, was measured respectively. Then, the A and B components of each group were redistributed and evenly coated on three boards. The coating amount of the three boards was 0.03 g / cm2. The boards were placed in an oven and the curing temperature and curing time were measured. See Table 2 for details. The curing temperature here is equal to the film-forming and curing temperature of the adhesive.
[0098] Table 1 Test results of each group of fabric samples
[0099]
[0100] Note: Color fastness is usually divided into 5 levels, where 1 indicates poor color fastness and 5 indicates excellent color fastness. The higher the color fastness level of fabric printing, the more stable the color of the fabric is, and the less likely it is to fade or bleed during wearing and washing, thus maintaining the appearance and quality of the clothing. The color fastness of normal fabrics is generally required to reach 3 to 4 levels to meet wearing needs.
[0101] If the stiffness of the printed pattern is high, it is not easy to deform when subjected to external force, so during the pushing process, the elongation length of the fabric sag contact detection line will be shorter. On the contrary, if the stiffness of the fabric sample is low, it is easier to deform, indicating that the printing is more flexible, so during the pushing process, the elongation length of the fabric sag contact detection line will be longer.
[0102] Air permeability is an important indicator to measure the breathability of fabrics. It indicates the rate at which air flows vertically through a sample under specified sample area, pressure drop and time conditions. The higher the air permeability, the better the breathability.
[0103] Table 2 Curing time and curing temperature of each group of adhesives
[0104] Group / Performance Operation time / s Curing temperature / ℃ Curing time / s Example 1 152 130 170 Example 2 158 139 176 Example 3 155 136 174 Comparative Example 1 204 167 322 Comparative Example 2 202 168 326 Comparative Example 3 189 146 334 Comparative Example 4 179 150 216 Comparative Example 5 171 146 210 Comparative Example 6 174 148 204
[0105] As shown in Table 1-2, in combination with Example 1 and Comparative Examples 1-2, the printing color fastness of the fabric sample of Example 1 is higher, indicating that the ink has better adhesion on the fabric, and the flexibility of the printing is better, and the curing temperature and time of the adhesive of Example 1 are reduced, which may be because the polyether polyols compounded by Mannich polyether polyol and soft foam polyether polyol are synergistic, and both have good compatibility with the prepolymer, and the compounding of the two has good reactivity, thereby accelerating the curing process of the polyurethane, and can also carry out effective curing reaction at a temperature of 130-140°C, without the need to use at a high temperature above 180°C, avoiding damage to the fabric by high temperature. At the same time, the compounding of the two also makes the adhesive better combined with the ink and fabric interface, reduces defects, improves adhesion, makes the fabric have good friction resistance and soap washing color fastness, and can also improve the softness of the fabric heat transfer printing, and has little effect on the air permeability of the printing.
[0106] Combining Example 1 with Comparative Example 3, it can be seen that when the total amount of composite polyether polyol is the same, the mass ratio of Mannich polyether polyol to soft foam polyether polyol is selected within the range of 1: (0.5-1), so that the adhesion, feel, air permeability, curing temperature and time of the printing on the fabric are all at a better level.
[0107] Combining Example 1 with Comparative Examples 4-6, it can be seen that butyl acetate and mesoporous microspheres can improve the adhesion and feel of the printing on the fabric to a certain extent and can reduce the curing temperature and time. The effect on the air permeability of the printing is greater. This may be because butyl acetate and mesoporous microspheres work together to improve the air permeability of polyurethane and significantly improve the air permeability of the printing, making the printed product more breathable and comfortable.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polyurethane adhesive, characterized in that: The invention is prepared from the following raw materials in weight percentage: 35-65wt% of composite polyether polyol, 14-25wt% of polyisocyanate, 1-5wt% of hydrophilic chain extender, 1-5wt% of small molecule chain extender, 0.05-3wt% of catalyst, 0.5-4wt% of neutralizer, 1-7wt% of end-capping agent, 1-8wt% of silane coupling agent, 2-12wt% of mesoporous microspheres, 2-5% of isopropanol, 2-5wt% of butyl acetate and 0.2-4wt% of defoaming agent, and the balance is water; wherein the composite polyether polyol is a composition of Mannich polyether polyol and soft foam polyether polyol in a mass ratio of 1:(0.5-1); the manufacturer of the soft foam polyether polyol is Shandong Bluestar Dongda Co., Ltd., the model is 10LD28XM, the number average molecular weight is 4000, and the functionality is 2; the manufacturer of the mesoporous microspheres is Shanghai Zhenzhun Biotechnology Co., Ltd., the model is MS-10040.
2. The polyurethane adhesive according to claim 1, characterized in that The silane coupling agent is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
3. The polyurethane adhesive according to claim 1, characterized in that The polyisocyanate is hydrogenated phenylmethane diisocyanate.
4. The polyurethane adhesive according to claim 1, characterized in that The catalyst is bismuth neodecanoate.
5. The polyurethane adhesive according to claim 1, characterized in that The raw material is selected from at least one of (I)-(III): (I) the small molecule chain extender is at least one of 1,4-butanediol, ethylene glycol, hexanediol, diethylene glycol, ethylenediamine, and diethylenetriamine; (II) The hydrophilic chain extender is 2,2-dimethylol propionic acid and / or 2,2-dimethylol butyric acid (III) The neutralizing agent is triethylamine.
6. The polyurethane adhesive according to claim 1, characterized in that The blocking agent is methyl ethyl ketone oxime.
7. The method for preparing the polyurethane adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Stir the polyether polyol, hydrophilic chain extender, silane coupling agent and mesoporous microspheres in a nitrogen atmosphere, then add polyisocyanate and catalyst, continue stirring and reacting at 70-95° C. for 1-4 hours, and then cool the reaction product to 60-70° C. for standby use; S2, adding a small molecule chain extender to the product obtained in S1, and then stirring the reaction for 1-2 hours, and gradually heating to 85-90°C; S3, adding the end-capping agent to the product obtained in S2, continuing to stir and react for 1-3 hours, then adding a neutralizing agent at room temperature, and adding water, butyl acetate and isopropanol for ultrasonic dispersion to obtain an aqueous polyurethane emulsion; S4, adding a defoamer to the aqueous polyurethane emulsion prepared in S3, dispersing and stirring, to obtain the polyurethane adhesive.
8. The method for preparing the polyurethane adhesive according to claim 7, characterized in that: In the step S1, the stirring speed is 500-600rpm; in the step S2, the stirring speed is 500-600rpm; in the step S3, the stirring speed is 500-600rpm, the ultrasonic power is 200-250W, and the ultrasonic time is 5-10min; in the step S4, the stirring speed is 500-600rpm, and the stirring time is 10-30min.
9. Use of the polyurethane adhesive according to any one of claims 1 to 6 in preparing clothing heat transfer coating ink.
Citation Information
Patent Citations
Preparation method of reactive polyurethane hot melt adhesive for fabric lamination
CN102336883A
Polymer fine particle-containing polyurethane curable composition having excellent mechanical strength
CN108368335A
Bio-based waterborne polyurethane as well as preparation method and application thereof
CN118063728A
Polyurethane foamcore for producing blades, in particular for wind power turbines
EP2461022A1
Adhesive and its preparation and application
US20200399512A1
Cited By
DTF pyrograph film and preparation method thereof
CN120003178A